2018
DOI: 10.1111/bph.14353
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to high‐internalizing δ opioid receptor agonist is critically mediated by arrestin 2

Abstract: Overall, these results suggest that δ receptor agonists interact with arrestins in a ligand-specific manner, and tolerance to high- but not low-internalizing agonists are preferentially regulated by arrestin 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…We observed no change in the analgesic efficacy of PN6047 over a 16-day dosing regimen. For comparison, a recent study reported that repeated treatment of mice (once daily; 10 mg/kg) with SNC80 resulted in analgesic tolerance within 3 days (Vicente-Sanchez et al, 2018). The lack of tolerance to PN6047 may in part arise as a consequence of its limited ability to induce internalization.…”
Section: Discussionmentioning
confidence: 99%
“…We observed no change in the analgesic efficacy of PN6047 over a 16-day dosing regimen. For comparison, a recent study reported that repeated treatment of mice (once daily; 10 mg/kg) with SNC80 resulted in analgesic tolerance within 3 days (Vicente-Sanchez et al, 2018). The lack of tolerance to PN6047 may in part arise as a consequence of its limited ability to induce internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, improved pharmacological characterization of opioid pathways has revealed that activation of an opioid receptor can trigger two distinct pathways, β-arrestin-dependent or β-arrestin-independent (i.e., G protein-mediated) and that these pathways differentially modulate antinociception and side effect profiles [9]. Despite the increasing number of studies that implicate δOR mediated β-arrestin recruitment with various (patho)physiological effects, such as tolerance [10], alcohol intake [11,12] and δOR agonist-induced seizures [10], the role of βarrestin recruitment towards δOR-induced cardioprotection remains unclear. From a translational perspective, peptide-based probes provide an ideal tool for studying the cardioprotective effects of the δOR, given their low brain penetration.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] As such, relatively few studies have systematically assessed this alternate pathway despite its important roles in regulating OR desensitization, and purported promotion of β-arrestin-dependent signal transduction through the scaffolding of various kinases. 15 An increasing number of studies have implicated δOR mediated β-arrestin recruitment with various (patho)physiological effects, ranging from tolerance, 16 alcohol intake 17,18 and δOR agonist-induced seizures. 16 To minimize these adverse effects, the development of "biased" ligands that can selectively activate the G protein pathway, without engaging the β-arrestinassociated pathways, 19 may provide a key set of pharmacological tools for reevaluating the drugability of δOR for several disease states.…”
Section: Introductionmentioning
confidence: 99%
“…15 An increasing number of studies have implicated δOR mediated β-arrestin recruitment with various (patho)physiological effects, ranging from tolerance, 16 alcohol intake 17,18 and δOR agonist-induced seizures. 16 To minimize these adverse effects, the development of "biased" ligands that can selectively activate the G protein pathway, without engaging the β-arrestinassociated pathways, 19 may provide a key set of pharmacological tools for reevaluating the drugability of δOR for several disease states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation